Pan Africa business simulation game - Cossa, G.; Roque, L. G.; Alturas, B.; Pinto, A. C. (2023 18th Iberian Conference on Information Systems and Technologies (CISTI), 2023)
Economists have demonstrated the existence of a positive correlation between management quality and the country's economic performance. In turn, business simulation games have shown their educational effectiveness in developing management skills crucial for African countries. However, its use is still incipient. Although they present different characteristics favourable to its implementation, for example: The African Continental Free Trade Area, the Digital Transformation Strategy Project for Africa (2020-2030) and The Pan-Africa Games Group, they also present singular characteristics such as the predominance of the informal sector, political instability and high corruption rates. These factors influence the design and adoption of a Pan-African Business Simulation Games Framework suitable for this specific context. This proposal aims to contribute a gaming framework to support collaborative development and appropriation by the end-users and Multi-User with content representative of their contextual diversity. The successful EVER project and Bootcamp created by the Mozambican firm ITIS, which adopted a lean startup methodology to add local content in Business Games, can serve as inspiration for the Pan African Business Simulations Games - PABSG.